Answer:
10
Step-by-step explanation:
Answer:
See below
Step-by-step explanation:
<h3>Part (a)</h3>
f(x - 1) is the translation of f(x) one unit right.
So the graph is exactly same shape but shifted right one unit.
<h3>Part (b)</h3>
f(x) has vertex (-1, 2)
<u>The function y = f(-x) + 2 will have the vertex changed as per rule:</u>
<u>So the new vertex is:</u>
- (-1, 2) → (-(-1), 2 + 2) = (1, 4)
Answer:
18.88
Step-by-step explanation:
16 x 1.18=18.88
In order to find this you need to assume that they are declared as X and as X + 2. This makes the formula for calculating it x (x+2)=483, and this, based on the formulas for calculation, equals
x^2+2x-83=0
From this we can see that a negative X is -23, which when +2 is added results in -21.